Progressive collapse resistance of cable net structures. (August 2022) - Vaezzadeh, Amin; Dolatshahi, Kiarash M.
Abstract: This study investigates the collapse resistance of the cable net structures. Compared to conventional structures, the analysis of the cable net structures is rather complicated due to the highly nonlinear behavior of the cables, which leads to large displacements and instabilities during the analysis. In this paper, 24 prototype structures are modeled with various force density levels, span lengths, and the number of spans. Several collapse scenarios, including the cable rupture, column removal, and restrain failure, are defined, and the prototype structures are analyzed considering 168 collapse scenarios. This paper aims to recognize the critical elements, the weak points, and other decisive parameters to protect the cable net structures against progressive collapse. The collapse analysis is performed using a step-by-step nonlinear pseudo-dynamic procedure considering the backbone curve for the elements to accurately model the rupture phenomenon. To verify the numerical approach, the results for one of the pseudo-dynamic analyses are compared against nonlinear and linear dynamic analyses using the Node Relaxation method. Analysis results indicate that the restrain failure is the most destructive collapse scenario for cable net structures. For multi-span cable nets, it is also concluded that the areas around the corner columns are more vulnerable to local damage.